Contraceptive prevalence and determinants among women of reproductive age group in Ogbomoso, Oyo State, Nigeria - Adeyemi AS; Olugbenga-Bello AI; Adeoye OA; Salawu MO; Aderinoye AA; Agbaje MA (Dove Medical Press, 2016)
Adewale S Adeyemi,1 Adenike I Olugbenga-Bello,2 Oluwatosin A Adeoye,3 Moshood O Salawu,3 Adesola A Aderinoye,3 Michael A Agbaje1 1Department of Obstetrics and Gynaecology, 2Department of Community Medicine, Faculty of Clinical Sciences, College of Health Sciences, Ladoke Akintola University of Technology (LAUTECH), Osogbo, Osun State, 3Department of Community Medicine, LAUTECH Teaching Hospital, Ogbomoso, Oyo State, Nigeria Background: The fertility rate in Nigeria is 5.7 children per woman. The contraceptive prevalence rate has been found to be low at 15% in 2013, compared to other countries such as the US and Pakistan. Objective: The study aimed to assess the contraceptive prevalence among women of reproductive age in Ogbomoso town, and determinants of use, with a view to make appropriate recommendations that will enhance the uptake of family planning services. Materials and methods: This is a descriptive cross-sectional study conducted with 560 respondents, using a multistage sampling technique. Data were retrieved using a semi-structured, pretested questionnaire. Results: All the respondents were aware of contraception; however, only 49.7% (271) had ever used any method, while 25.4% (69) of the number who had ever used contraception were currently using a method. The methods being used were the traditional type (four [5.9%]), natural type (two [3.0%]), and modern type (63 [91.1%]). The predictors of contraception use included the age group of 40–49 years (odds ratio [OR] 14.1; confidence interval [CI] 3.06–73.24; P=0.0001); the married women were approximately four times more likely to use contraception than the single women (OR 4.5; CI 3.03–6.72; P<0.0001). The women with tertiary level of education were three times more likely to use contraception than those without formal education (OR 3.1; CI 1.13–9.95; P=0.0268), and the odds ratio of respondents with a positive attitude to using contraception more than those with negative attitude was 2 (OR 2; CI 1.41–2.91; P<0.0001). Conclusion: In light of the advantages associated with contraception use, there needs to be a conscious effort, especially among health care workers, to educate women about contraception and encourage its use. Keywords: contraception, women of reproductive age, prevalence, determinants